The Journalist's Tort Responsibility and The Ways To Avoid It In Light of The Saudi Press And Publication System: An Analytical Study - Aisha Mohamed Ismail Elamin (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
This study aims to determine the tort responsibility of the journalist in case of violating the rights of individuals and the extent of the possibility to avoid the tort responsibility of the journalist. This can happen through the decisions of the competent committees to consider violations of the provisions of the Saudi Press and Publication Law, based on the reasoning of its decisions on Article (9) of the Saudi Press and Publication Law. In the research, the analytical approach is used to the relevant texts from the Saudi Press and Publication System and the applied approach, which is based on strengthening legal and legal positions with judicial positions. In this study, the author addresses the pillars of the tort responsibility of the journalist by highlighting the pillars of Tort and damage, with the possibility of pushing the journalist to tort responsibility through satisfaction with the publication and the right to objective criticism. The study recommended: reorganizing the journalist’s tort responsibility through the inclusion of legal texts in the publications and publishing system due to the absence of legalization of financial transactions, which shows the general rules of responsibility, and publishing the decisions of the competent committees to consider violations of the provisions of the Saudi Press and Publication Law as a result of the absence of legalization of civil transactions.Keywords: Journalist Tort; Human Dignity; Privacy; Moral Damage; Objective Criticism Tanggung Jawab Kerugian Wartawan dan Cara Menghindarinya Berdasarkan Sistem Publikasi dan Pers Saudi: Sebuah Studi Analitis Abstrak:Penelitian ini bertujuan untuk mengetahui tanggung jawab gugatan wartawan dalam kasus pelanggaran hak-hak individu dan sejauh mana kemungkinan untuk menghindari tanggung jawab gugatan wartawan. Hal ini dapat terjadi melalui keputusan komite yang berwenang untuk mempertimbangkan pelanggaran ketentuan Undang-Undang Pers dan Publikasi Saudi, berdasarkan pertimbangan keputusannya pada Pasal (9) Undang-Undang Pers dan Publikasi Saudi. Dalam penelitian ini, pendekatan analitis digunakan pada teks-teks yang relevan dari Saudi Press and Publication System dan pendekatan terapan, yang didasarkan pada penguatan posisi hukum dan hukum dengan posisi yudisial. Dalam studi ini, penulis membahas pilar-pilar tanggung jawab kerugian jurnalis dengan menyoroti pilar-pilar kerugian dan kerugian, dengan kemungkinan mendorong jurnalis untuk melakukan tanggung jawab kerugian melalui kepuasan terhadap publikasi dan hak atas kritik yang objektif. Kajian ini merekomendasikan: menata kembali tanggung jawab wanprestasi jurnalis melalui pencantuman teks hukum dalam sistem penerbitan dan penerbitan karena tidak adanya legalisasi transaksi keuangan, yang menunjukkan aturan umum pertanggungjawaban, dan mempublikasikan keputusan komite yang berwenang untuk mempertimbangkan pelanggaran. ketentuan Hukum Pers dan Publikasi Saudi sebagai akibat tidak adanya legalisasi transaksi perdata.Kata Kunci: Gugatan Wartawan; Harga diri manusia; Pribadi; Kerusakan Moral; Kritik Objektif Деликатная ответственность журналиста и способы ее избежать в свете саудовской прессы и системы публикаций: аналитическое исследованиеАбстрактный:Это исследование направлено на определение деликтной ответственности журналиста в случае нарушения прав человека и степени возможности избежать деликтной ответственности журналиста. Это может произойти в результате решений компетентных комитетов о рассмотрении нарушений положений Закона Саудовской Аравии о печати и публикациях на основании обоснования своих решений по статье (9) Закона Саудовской Аравии о печати и публикациях. В исследовании используется аналитический подход к релевантным текстам из Саудовской системы печати и публикаций и прикладной подход, который основан на усилении юридических и юридических позиций с помощью судебных позиций. В этом исследовании автор обращается к столпам деликтной ответственности журналиста, выделяя столпы деликта и ущерба, с возможностью подтолкнуть журналиста к деликтной ответственности через удовлетворение публикацией и право на объективную критику. В исследовании рекомендовалось: реорганизовать деликтную ответственность журналиста путем включения юридических текстов в системы публикаций и публикации в связи с отсутствием легализации финансовых операций, которая показывает общие правила ответственности, и опубликовать решения компетентных комитетов по рассмотрению нарушений. положений Закона о печати и публикациях Саудовской Аравии в результате отсутствия легализации гражданских сделок.Ключевые слова: журналист Tort; Человеческое достоинство; Конфиденциальность; Моральный урон; Объективная критика